Task dependent muscular volume in unilateral edentulous patients by magnetic resonance imaging (MRI) - Shokry, Shereen M.; Salam, Zeinab Abdel; Ahmed, Abdel Wahab S.; Ali, Ehab Ismail (Archives of Oral Research, 2012)
Objective: To assess the sequelae of unilateral chewing on muscles of mastication via comparing the approximatemuscular volume (AMV) of the masseter (MM), medial pterygoid (MPM), temporalis (TM), superior and inferior lateral pterygoid muscles (SLPM/ILPM) bilaterally using MRI. Materials and methods: Twenty patients (16 females and 4 males) were selected from outpatient dental clinics of Kaser Al Aini Hospitals, Cairo University, complaining from being unilaterally edentulous for one year or more. Also six fully dentate individuals (2 males and 4 females) were selected as control group. Magnetic Resonance Imaging (MRI) of the masticatory muscles was performed followed by measuring the approximate muscle volume (AMV) for each muscle bilaterally using the planimetry method. Results: Showed increase in the approximate muscular volume (AMV) of the dentate side in both right side and left side edentulous patients. Conclusion: Our study shows the effect of long term unilateral chewing on decreasing the AMV in the nonfunctioning side, suggesting that measuring the approximate masticatory muscle volume using MRI could be helpful in detection of long-term functional disability of each muscle in comparison to adjacent muscles.